Subacute cadmium exposure promotes M1 macrophage polarization through oxidative stress-evoked inflammatory response and induces porcine adrenal fibrosis. (September 2021) - Yao, Yujie; Zhao, Xia; Zheng, Shufang; Wang, Shengchen; Liu, Honggui; Xu, Shiwen
Graphical abstract: Highlights: Cd exposure leads to fibrosis in porcine adrenal gland. Cd exposure causes imbalance of M1/M2 in porcine adrenal gland. Cd promotes M1 polarization through oxidative stress-evoked TLR4/NF-κB/NLRP3 pathway. M1 polarization promotes porcine adrenal fibrosis through TGF-β1/Smad2/3 signaling. Abstract: Cadmium (Cd) is a widely distributed environmental pollutant with immunotoxicity and endocrine toxicity. M1/M2 macrophages participate in the immune response and exert an essential influence on fibrosis. Nevertheless, whether Cd can induce porcineadrenal fibrosis by affecting the polarization of M1/M2 macrophages and its potential regulatory mechanism have not been explored. We added 20 mg/kg CdCl2 to the pig diet for 40 days to investigate the fibrogenic effect of subacute Cd exposure on the adrenal gland. The results indicated that the ACTH and CORT in serum were decreased by 15.26 % and 21.99 %, respectively. The contents of adrenal mineral elements Cd, Cr, Mn were increased up to 34, 1.93, 1.42 folds and Co, Zn, Sn were reduced by 21.57 %, 20.52 %, 15.75 %. Concurrently, the pro-oxidative indicators (LPO, MDA and H2 O2 ) were increased by 1.85, 2.20, 2.77 folds and 3.60, 11.15, 4.11 folds upregulated mRNA levels of TLR4, NF-κB, NLRP3 were observed. Subsequently, the expression of M1 macrophages polarization markers (IL-6, iNOS, TNF-α, CCL2 and CXCL9) were raised by 2.03, 2.30, 2.35, 1.58, 1.56 folds, while M2 macrophages (IL-4, CCL24, Arg1, IL-10, MRC1) showed a 62.34 %, 31.88 %, 50.26 %, 74.00 %, 69.34 % downregulation. The expression levels of AMPK subunits and genes related to glycolysis, oxidative phosphorylation (OXPHOS) and fatty acid oxidation (FAO) were also markedly increased. Additionally, the expression level of TGF-β1, Smad2/3 and downstream pro-fibrotic markers was obviously upregulated. Taken together, we conclude that Cd activates the oxidative stress-mediated TLR4/NF-κB/NLRP3 inflammatory signal transduction, leading to porcine adrenal fibrosis by promoting macrophage polarization toward M1.